Implementation of User Centered Design Method on CarbonArea Website User Experience - Meilani Jesica Tiodora; Evlyn Jane Putri; Devi Fitrianingsih; Irfan Tigranaufal Nugraha; Danke Hidayat; Ramma Dwi Rachmat; Mahatmadi Ariq Mayangkara; Ade Riyanti; Afifah Rodhiyatun Nisa (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
This study aims to evaluate the application of the User-Centered Design (UCD) approach in designing the user interface (UI) and user experience (UX) of the CarbonArea website, which provides information on the impact of carbon dioxide (CO2) on food security. The research methodology included interviews with potential users, a literature review, as well as iterative stages of UCD, including understanding the context of use, identifying user needs, designing a solution, and conducting a design evaluation. The interview results revealed that users wanted interactive features such as maps and graphs for real-time monitoring of CO2 levels. The application of UCD proved effective in creating a design that meets user needs, while improving user experience and website attractiveness.